ответ 4
https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cleft%20%5C%7B%20%5Cbegin%7Barray%7D%7Blcl%7D%203x%2B14%20%5Cgeq%204-x%20%5C%5C%20%5C%5C%20%5Cfrac%7B5x-1%7D%7B4%7D%20-%20%5Cfrac%7Bx-1%7D%7B2%7D%20%5Cgeq%203x-2%2C%20~%20%5CBig%20%7C%5Ctimes%204%20%5Cend%7Barray%7D%20%5Cright.%20%5C%5C%20%5C%5C%20%5C%5C%20%5C%5C%20%5Cleft%20%5C%7B%20%5Cbegin%7Barray%7D%7Blcl%7D%203x%2Bx%20%5Cgeq%204-14%20%5C%5C%20%5C%5C%20(5x-1)%20-%202(x-1)%20%5Cgeq%204(3x-2)%20%5Cend%7Barray%7D%20%5Cright.%20%5C%5C%20%5C%5C%20%5C%5C%20%5C%5C%20%5Cleft%20%5C%7B%20%5Cbegin%7Barray%7D%7Blcl%7D%204x%20%5Cgeq%20-10%20%5C%5C%20%5C%5C%205x-1%20-%202x%2B2%20%5Cgeq%2012x-8%20%5Cend%7Barray%7D%20%5Cright.
1. u = 7-2v
(7-2v)^2 + 4v - 13 =0
49 - 28v + 4v^2 + 4v - 13 = 0
4v^2 - 24v + 36 = 0 (:4)
v^2 - 6v + 9 = 0
(v - 3)^2 = 0
v =3
u = 7 - 2*3 = 7-6=1
ответ : v=3, u=1
2. z = -3+y^2
y^2 + 3*(y^2-3)-7=0
y^2 +3y^2 - 9-7 = 0
4y^2 - 16 = 0
4*(y^2-4)=0
y = 2 y=-2
z = 4-3=1 z = 4-3=0
ответ : y = 2, z=1; y=-2, z=1
3. m = 7+2n
(7+2n)^2 +5n + 14 = 0
49 + 28n + 4n^2 + 5n + 14 = 0
4n^2 + 33n + 65 = 0
D = 1089 - 1040 = 49
n1 = -33+7/8 = -26/8 = -3,25
n2= -33-7/8 = -40/8 = -5
m1 = 7 - 2 * 26/8 = 7-6,5 = 0,5
m2 = 7 - 2*5 = 7-10 = -3
ответ : n=-3,25,m=0,5 ; n=-5, m=-3
4. 2k = 7+2t^2
k = 7+2t^2/2
3*(7+2t^2/2) + 5t - 20 = 0
6t^2 + 10t - 19 = 0
D = 784
t1 = 1,5
t2 = -19/6
k1 = 5,75
k2 = 13 19/36
Привет дершепо7еелоролррро